Índice de masa corporal frente al concepto de autoimagen corporal en profesionales de estética (2019)
Self-concept of body image is important when generating definitions about body care by professionals in esthetic centers. The objective of this research was to compare the body mass index with the measurement of body self-image in a group of workers of an esthetic center. A descriptive cross-sectional study was carried out in the period from February to June 2018 at an esthetic center in Bogotá. The study population consisted of 31 individuals, with an average age of 28.77 ± 8.11 years. Statistically significant differences were found between the self-perception of body silhouette and the body mass index perception compared to the one evaluated. Therefore, it is important to establish the concept of body image in workers, which favors the self-concept of body care. This in order to transcend behaviors of healthy habits for disease prevention and control in the behavior of public health indicators.